Increased soluble VCAM-1 serum levels in preeclampsia are not correlated to urinary excretion or circadian blood pressure rhythm - Heyl, Wolfgang; Heintz, B.; Reister, F.; Harwig, S.; Witte, Klaus; Lemmer, Björn; Rath, W. (Journal of perinatal medicine, 2005)
Objective : Soluble vascular cell adhesion molecule-1 (VCAM-1) is known to be elevated in serum of patients with preeclampsia, but there are no data available on the significance of urinary VCAM-1 excretion in preeclampsia. The aim of our study was to uncover possible circadian rhythms of VCAM-1 plasma levels and urinary VCAM-1 excretion in uncomplicated and hypertensive pregnancies and to ascertain their relation to blood pressure. Study design : A total of 10 normotensive and 10 preeclamptic pregnant women were included in this study. Venous blood was collected hourly, and urine samples were taken every 2 h over a period of 24 h. VCAM-1 levels were determined by ELISA. We compared these results with the circadian blood pressure rhythm. Results : The median VCAM-1 plasma levels were significantly (P<0.01) increased in preeclamptic patients (851.5 ng/mL) in comparison to normotensive pregnant women (659.3 ng/mL) without any circadian rhythm being apparent; however, the urinary excretion of VCAM-1 showed a typical circadian rhythm, with a higher excretion rate during daytime. Conclusion : For the first time we have demonstrated that urinary VCAM-1 excretion in pregnancy shows a circadian rhythm without correlation to plasma levels or the circadian blood pressure rhythm. In contrast, VCAM-1 serum levels did not show a diurnal rhythm. We assume that VCAM-1 serum levels do not correlate with systemic blood pressure or urinary excretion.
Gesehen am 07.04.2022